Fraud Dalam Lembaga Keuangan Syariah: Analisis Jenis, Faktor Penyebab, dan Strategi Pencegahan Dalam Perspektif Ekonomi Syariah - Dhiyaa meuthia; Septianor Nugraha (Program Studi Ekonomi Syariah IAIN Parepare, 2026)
Fraud is one of the major challenges faced by Islamic financial institutions because it can undermine integrity, stability, and public trust, despite their operations being based on the principles of trustworthiness (amanah), justice, and transparency. This study aims to analyze the types of fraud occurring in Islamic financial institutions, identify the factors contributing to such fraud, and examine prevention strategies from the perspective of Islamic economics. The research employs a qualitative method using a library research approach, drawing on various sources, including scientific journals, books, and relevant academic publications. The findings indicate that fraud in Islamic financial institutions includes asset misappropriation, abuse of authority, money laundering, collusion in financial statement fraud, and cyberattacks. The factors contributing to fraud consist of pressure, opportunity, rationalization, weak implementation of Good Corporate Governance (GCG), and inadequate understanding and application of Islamic principles. Fraud prevention strategies include strengthening internal control systems, optimizing audits and whistleblowing systems, enhancing supervision by the Sharia Supervisory Board, enforcing strict sanctions, and internalizing the values of trustworthiness, integrity, and Sharia compliance within organizational culture. This study contributes to a deeper understanding of the forms of fraud and prevention efforts, serving as a reference for the development of more effective governance and control systems in Islamic financial institutions.